Incidence and prevalence of multiple sclerosis in China and other Asian countries - G.X. Zhang; A. Carrillo-Vico; W.T. Zhang; S.S. Gao; G. Izquierdo Ayuso (Neurología (English Edition), 2023)
The prevalence of multiple sclerosis (MS) in Asian countries is thought to be lower than in Western countries, with Asian populations presenting 80% less risk of MS than white populations. Incidence and prevalence rates in Asian countries are therefore not well defined and their association with rates in neighboring countries, as well as with ethnic, environmental, and socioeconomic factors, are not well understood.We performed a comprehensive literature review of epidemiological data from China and neighbouring countries to study the frequency of the disease, focusing on prevalence, and the progression over time and the influence of sex-related, environmental, dietary, and sociocultural factors.Prevalence rates in China range between 0.88 cases/100,000 population in 1986 and 5.2 cases/100,000 population in 2013, with a non-significant upwards trend (p = .08). The increase observed in Japan, where figures ranged between 8.1 and 18.6 cases/100,000 population was highly significant (p < .001). Prevalence rates in countries with predominantly white populations are considerably higher and have increased over time, reaching 115 cases/100,000 population in 2015 (r2 = 0.79, p < .0001).In conclusion, the prevalence of MS in China appears to have risen in recent years, although Asian populations (including Chinese and Japanese populations, among others) appear to present less risk than other populations. Within Asia, geographical latitude appears not to be a determining factor for developing MS. Resumen: La prevalencia de la esclerosis múltiple (EM) en los países asiáticos se considera que es más baja que en los países occidentales, las poblaciones asiáticas tienen un 80% menos de riesgo de EM que las caucásicas. No se conocen bien las cifras de incidencia, prevalencia y su relación con otros países de su entorno y su relación con factores étnicos, ambientales y socioeconómicos.Hemos realizado una revisión bibliográfica exhaustiva de los datos epidemiológicos existentes en China y países limítrofes, para estudiar la frecuencia de la enfermedad, centrándonos en la prevalencia, sus cambios evolutivos a lo largo del tiempo y su relación con factores de género, ambientales, alimenticios y socioculturales.La prevalencia en China oscila en cifras que van desde 0,88 en 1986 a 5,2 en 2013 por 100.000 habitantes con una tendencia a aumentar que no es estadísticamente significativa (p = 0,08), mientras que en Japón este incremento es muy significativo, con cifras que oscilan entre 8,1 y 18,6 (p < 0,001). La prevalencia en los países donde predomina la raza caucásica son mucho más elevadas y aumentan con el tiempo, llegando a 115 por 100.000 habitantes en 2015 (r2 = 0,79, p = 0,0001).En conclusión, la prevalencia de la EM en China parece está aumentando en los últimos años, aunque la raza amarilla (chinos y japoneses, entre otros) tienen menor riesgo de padecerla que el resto de las poblaciones. La latitud no parece ser un factor muy determinante en Asia para presentar un mayor riesgo de padecer EM.